Pengembangan E-Worksheet Problem Based Learning Berbantuan Augmented Reality untuk Meningkatkan Literasi Sains dan Berpikir Kritis pada Materi Entomologi Pertanian - Bebi Ramalia Alfi; Nur Aeni Ariyanti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop and evaluate an Augmented Reality (AR)-assisted Problem Based Learning (PBL) E-Worksheet in Agricultural Entomology that is valid, practical, and effective in improving science literacy and critical thinking skills of Biology Education students. The method used was Research and Development employing the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. Field testing was conducted with eighth-semester students of the Biology Education Study Program at Universitas Pasundan using questionnaires, interviews, observations, and tests as research instruments. Data were analyzed using descriptive statistics and MANOVA. The  results showed that the AR-assisted PBL E-Worksheet was highly feasible in terms of accessibility, content substance, presentation, characteristics, and language, and was categorized as highly practical based on lecturers’ and students’ responses. The use of the E-Worksheet also had a significant simultaneous effect on students’ science literacy and critical thinking skills. In conclusion, the AR-assisted PBL E-Worksheet in Agricultural Entomology is feasible, practical, and effective as a learning medium to support the improvement of science literacy and critical thinking skills among prospective biology teachers.  Keywords: Augmented Reality, Critical Thinking, Problem Based Learning, Science Literacy